Therapeutic Analysis of Bay Leaf Decoction as an Intervention of Acute Pain Nursing Problems With Hypertension - Arita Murwani; Nur Alfiyanti; Ana Nur Hikmawati; Ani Mashunatul (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Health problems can arise at a stage according to family development, one of which is the development of elderly families. A problem that often arises in the elderly is Hypertension. Medical management of hypertension, one of which is medicinal and non-medical, namely herbal medicine with bay leaf decoction. Prevention of hypertension one is by means of complementary therapy, namely bay leaf decoction. This study aimed to analyze bay leaf decoction therapy in hypertensive clients with acute pain nursing problems at the stage of development of elderly families. The research method used is descriptive, the implementation of research by providing bay leaf decoction therapy for 3 days drunk morning and evening. The results of acute pain problems were resolved before the patient's TD therapy was 170/100 mmHg, and after bay leaf decoction therapy, the patient's TD became 150/80 mmHg. The patient's pain also decreased from a scale of 6 to a scale of 3. It can be concluded that there is a hypertension-related influence on the elderly with pain problems with bay leaf decoction therapy